Levels of Some Proinflammatory Cytokines in Obese Women with Polycystic Ovary Syndrome after Metformin Therapy - Ateia, Yaser Abbas; Saleh, Eman Mahdi; Abdullah, Thikra N.; Al Musawee, Zynab (AL-Kindy College Medical Journal, 2013)
Background: Polycystic ovary syndrome is a heterogeneous disorder and its etiology appears to be complex and multifactorial; characterized by hyperandrogenism, chronic anovulation and infertility. It’s associated with evidence of low-grade chronic inflammation, as indicated by the presence of elevated levels of high sensitive C- reactive protein levels, interleukin-6 and tumor necrosis factor-α. The source of excess circulating tumor necrosis factor-α in obese Polycystic ovary syndrome patient is likely to be the adipose tissues while in lean women increased visceral adiposity has been proposed as a source of excess tumor necrosis factor-α.Objectives: to evaluate the levels of high sensitive C- reactive protein, tumor necrosis factor-α and interleukin-6 in patients with polycystic ovary syndrome before and after treatment with metformin; with emphasis on their relationship with the improvement in ovulation rate and body mass index in Iraqi women.Methods: 69 Iraqi females with PCOS, with mean age of 25.8±4.4 years, body mass index 31.14±2.23 kg/m2 and insulin resistant equal to 3.15±0.25. Additionally, 30 healthy fertile women BMI= 26.87±3.1 kg/m2 and mean age 23.4±2.8 years), the patients were treated with metformin 1500 mg/day for 3 months. Blood samples were obtained in the morning subsequent to an overnight fasting at baseline and at the end of the 12 weeks period of treatment, the samples were analyzed for plasma glucose level estimated by enzymatic colorimetric kit, while serum insulin , TNF-α, IL-6 , hs-CRP, Progesterone and sex hormone binding globulin . Results: BMI values were significantly increased at baseline value in patients (P